A three-dimensional finite element analysis of interface delamination in a ductile film/hard substrate system induced by wedge indentation - She, Chongmin; Zhang, Yong-Wei; Zeng, Kai-Yang (Engineering fracture mechanics, 2009)
Interface delamination and arching of a ductile thin film on a hard substrate subject to microwedge indentation were investigated systematically using a three-dimensional finite element method. A traction–separation law was introduced to simulate the cohesion and failure behavior of the interface between the film and the substrate. The effects of the interface strength and the length of the microwedge indenter on the onset and growth of interface delamination and film arching were analyzed. It was shown that a two-dimensional to three-dimensional transition of stress state occurs during indentation, depending on the indenter length and indentation depth. Conditions for using two-dimensional and three-dimensional models were suggested.